2014
DOI: 10.1007/s10236-014-0695-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling-based assessment of suspended sediment dynamics in a hypertidal estuarine channel

Abstract: We investigate the dynamics of suspended sediment transport in a hypertidal estuarine channel which displays a vertically sheared exchange flow. We apply a three-dimensional process-based model coupling hydrodynamics, turbulence, and sediment transport to the Dee Estuary, in the north-west region of the UK. The numerical model is used to reproduce observations of suspended sediment and to assess physical processes responsible for the observed suspended sediment concentration patterns.The study period focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…Classical links between turbulent properties and flocs in the Dee Estuary following which aggregation occurs during periods of weak turbulence (slack water at low and high tide) and break-up during periods of intense turbulence (maximum flood or ebb current) have been reported (e.g., Thurston, 2009;Ramírez-Mendoza et al, 2014) and included in numerical models . Amoudry et al (2014) highlighted the importance of horizontal gradients in suspended sediment, themselves due to gradients in turbulence and bed sediment distribution, toward reproducing observed SPM behaviour in the Hilbre Channel.…”
Section: Accepted Manuscriptmentioning
confidence: 70%
See 1 more Smart Citation
“…Classical links between turbulent properties and flocs in the Dee Estuary following which aggregation occurs during periods of weak turbulence (slack water at low and high tide) and break-up during periods of intense turbulence (maximum flood or ebb current) have been reported (e.g., Thurston, 2009;Ramírez-Mendoza et al, 2014) and included in numerical models . Amoudry et al (2014) highlighted the importance of horizontal gradients in suspended sediment, themselves due to gradients in turbulence and bed sediment distribution, toward reproducing observed SPM behaviour in the Hilbre Channel.…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…Observations of suspended sediment concentration to the northwest of the estuary entrance, still in the Liverpool Bay, were of about 24 mg•l −1 in winter and 5 mg•l −1 in summer with size of about 100 μm for both suspended sediments at the surface and near the bottom (Krivtsov et al, 2008). At the entrance of the estuary, in the Hilbre Channel, Amoudry et al (2014) reported maximum suspended sediment concentration of 500 mg•l −1 and Bolaños and Souza (2010) found dominance of fine flocs of about 70 μm in both channels. Inside the estuary, early measurements from bed samples by Turner et al (1994) showed that the sediment fraction below 63 μm was present in percentages between 23% and 62%.…”
Section: Accepted M Manuscriptmentioning
confidence: 96%
“…However, validation has shown it is still capable of simulating the frontal position, although the small scale variability is lost requiring the need for an additional high resolution nest in Liverpool Bay (Bricheno et al, 2014). Numerous studies validating the third 180 m nested model against observations (e.g., Bolaños et al, 2013;Brown et al, 2013;Amoudry et al, 2014;Bricheno et al, 2014;Ramirez-Mendoza et al, 2014;Brown et al, 2015) gives confidence in this 1.8 km to 180 m nested configuration.…”
Section: Model Setupmentioning
confidence: 99%
“…The Liverpool Bay model is therefore setup to cover the ROFI, which includes two strategic UK coastal management zones (Cooper and Pontee, 2006). Both the 1.8 km and 180 m models have been proven to accurately simulate: sea surface elevation at tide gauge locations (Brown and Wolf, 2009;Brown 2010) and Acoustic Doppler Current Profiler (ADCP) locations ; velocity components at ADCP sites Amoudry et al, 2014;Brown et al, 2015); and the frontal position compared with sea surface temperature (SST) from satellite imagery (Bricheno et al, 2014;Hopkins and Polton, 2012), focusing particularly on the 17 th February 2008 (Bricheno et al, 2014). In the case of the 1.8 km model further validation of temperature and salinity fields has been carried against Ferry Box observations (O 'Neill et al, 2012) and Conductivity, Temperature and Depth (CTD) observations (O'Neill et al, 2012;Polton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Amoudry et al (2014) use a numerical model to examine the mechanisms affecting the variability of the suspended sediment distribution of suspended sediment in the macro-tidal Dee estuary. They find that advection and resuspension are much more important than riverine input of sediment, and the variability is particularly sensitive to settling velocity (and associated particle size).…”
Section: Estuarine Sediment Transportmentioning
confidence: 99%